2017 International Conference on Wireless Communications, Signal Processing and Networking (WiSPNET) 2017
DOI: 10.1109/wispnet.2017.8300154
|View full text |Cite
|
Sign up to set email alerts
|

Pixel normalization from numeric data as input to neural networks: For machine learning and image processing

Abstract: Text to image transformation for input to neural networks requires intermediate steps. This paper attempts to present a new approach to pixel normalization so as to convert textual data into image, suitable as input for neural networks. This method can be further improved by its Graphics Processing Unit (GPU) implementation to provide significant speedup in computational time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A previous report presented the idea of converting numeric data to images and the possibility of using them in image classification 5 . Our novel idea was to convert various type of clinical data, involving not only numeric but also general examination data, into a simple image.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report presented the idea of converting numeric data to images and the possibility of using them in image classification 5 . Our novel idea was to convert various type of clinical data, involving not only numeric but also general examination data, into a simple image.…”
Section: Discussionmentioning
confidence: 99%
“…The basic principles of CNN operation are described in papers [3,10]. Studies [7][8][9] considered methods for encoding numerical data using images and solving a classification problem.…”
Section: Review Of Known Methods Of Data Conversion and Nn Learningmentioning
confidence: 99%
“…Paper [9] examined a method to normalize text data for their subsequent conversion into graphical data. It is shown that the application of the min-max normalization makes it possible to retain the scale of data and generates the entire data set in the same range that is critical for certain tasks.…”
Section: Review Of Known Methods Of Data Conversion and Nn Learningmentioning
confidence: 99%
See 2 more Smart Citations